The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2136/sssaj2008.0049
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tree Species, Nitrogen Fertilization, and Soil C to N ratio on Gross Soil Nitrogen Transformations

Abstract: To investigate controls on gross N transformations in forest soils, a 15N pool dilution technique was used on soils of single‐species plots of five major tree species (red oak [Quercus rubra L.], sugar maple[Acer saccharum Marsh.], hemlock [Tsuga canadensis (L.) Carr], beech [Fagus grandifolia Ehrh.] and yellow birch [Betula alleghaniensis Britton]) in the Catskill Mountains of New York State. Catskill forest soils had high rates of gross mineralization and NH4+ consumption, indicating rapid NH4+ cycling, a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
33
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 50 publications
9
33
2
4
Order By: Relevance
“…to NO 3 -was similar in both forest soils (*0.1 lg N g -1 day -1 ) and four to nine times lower than the gross N mineralization rate. While higher nitrification rates have been reported for temperate forest soils (Booth et al 2005;Christenson et al 2009;Verchot et al 2001), the current values exceed rates measured in the same region (Vervaet et al 2004). At Harvard Forest, mineral soils of deciduous and pine forests had similar gross nitrification rates (Venterea et al 2004).…”
Section: Production and Consumption Of Nitratecontrasting
confidence: 62%
See 2 more Smart Citations
“…to NO 3 -was similar in both forest soils (*0.1 lg N g -1 day -1 ) and four to nine times lower than the gross N mineralization rate. While higher nitrification rates have been reported for temperate forest soils (Booth et al 2005;Christenson et al 2009;Verchot et al 2001), the current values exceed rates measured in the same region (Vervaet et al 2004). At Harvard Forest, mineral soils of deciduous and pine forests had similar gross nitrification rates (Venterea et al 2004).…”
Section: Production and Consumption Of Nitratecontrasting
confidence: 62%
“…Nitrogen cycling in forest soils can vary among the dominant tree species (Christenson et al 2009;Lovett et al 2004;Yan et al 2008;Zeller et al 2007) because tree species affect physicochemical and biological characteristics of soils (Binkley and Giardina 1998). Soil microbial biomass, activity, and community structure can thus be tree species dependent (Hackl et al 2005;Priha et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, deciduous forests with lower soil C:N ratios may have higher gross nitrification rates comparable to the other biomes in our study. Cross-site comparisons of forests that included both deciduous and coniferous trees have also documented negative relationships between soil C:N ratios and both gross nitrification (Bengtsson et al, 2003;Christenson et al, 2009) and net nitrification (Lovett et al, 2004;Venterea et al, 2003). Christenson et al (2009) found lower gross nitrification rates in forests with lower gross mineralization rates and hypothesized that NH 4 þ supply likely limited nitrification in mineral soil horizons.…”
Section: Patterns In and Controls On Nitrificationmentioning
confidence: 99%
“…Cross-site comparisons of forests that included both deciduous and coniferous trees have also documented negative relationships between soil C:N ratios and both gross nitrification (Bengtsson et al, 2003;Christenson et al, 2009) and net nitrification (Lovett et al, 2004;Venterea et al, 2003). Christenson et al (2009) found lower gross nitrification rates in forests with lower gross mineralization rates and hypothesized that NH 4 þ supply likely limited nitrification in mineral soil horizons. In support of this hypothesis, the meta-analysis by Booth et al (2005) showed that gross N mineralization was the strongest predictor of gross nitrification (with R 2 ¼ 0.32) across woody, grassland, and agricultural ecosystems.…”
Section: Patterns In and Controls On Nitrificationmentioning
confidence: 99%